Gambaran Persepsi Masyarakat Penerima Vaksin Covid-19 di Desa Penfui Timur RT 18 - Ferdinandus Ju; Marylin Susanti Junias; Indriati A. Tedju Hinga (Yayasan Literasi Sains Indonesia, 2023)
The Covid-19 vaccine is one of the government's breakthroughs to fight and deal with Covid-19 in the world, especially Indonesia. The goal of the Covid-19 vaccination is to reduce the spread of Covid-19, reduce the morbidity and mortality caused by Covid-19, achieve immunity and protect the public from Covid-19, so that it can protect society and the economy. This study aims to describe the Perception of the Community Recipient of the Covid-19 Vaccine in East Penfui Village Rt.18. This research was conducted using a type of qualitative research using a descriptive survey method. The population in this study is all the people in RT 18, East Penfui Village. The population of this research study is the people who live in RT 18, East Penfui Village with a total of 400 people and the sampling technique uses simple random sampling technique with a sample size of 200 people. The results showed that the majority of the people of RT 18, East Penfui Village believed in the safety and availability of the Covid-19 vaccine, namely 137 residents or 68.5%, while 63 residents (32.5%) were unsure about the safety and availability of the vaccine. Covid-19. the entire community of RT 18, East Penfui Village has received the Covid-19 vaccine under the brands Sinovac, Astrazeneca, Pfizer, Novavax, Moderna and with the complete dose, namely the first dose and the second dose (100%). The people of RT 18, East Penfui Village gave an unfavorable response or reaction to the addition of the third dose of the Covid-19 vaccine, namely 104 residents (52%). Suggestions for the Government Provide education about the importance of the Covid-19 vaccine and strive to foster a sense of trust, safety, and comfort in administering the Covid-19 vaccine.